2022
DOI: 10.3390/jcm11175126
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Surgery Improves Hypogonadism and Sexual Function in Men without Effects in Sperm Quality

Abstract: (1) Background: Obesity is associated with hypogonadism, sexual dysfunction, and impaired fertility in men. However, its effects on semen parameters or sexual function remain debatable. (2) Methods: This paper involves a longitudinal study in men submitted for obesity surgery at a university tertiary hospital. Patients were studied at baseline and at 6, 12, and 18 months after obesity surgery. At each visit, anthropometry measures were collected and hormonal and semen parameters were studied. Sexual function w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Another study by Inka et al [30] showed no effect of bariatric surgery on sperm count or sperm attention at any time during the study period. Likewise, there is little information on the effect of Diet-Induced Weight Loss on sperm parameters.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Another study by Inka et al [30] showed no effect of bariatric surgery on sperm count or sperm attention at any time during the study period. Likewise, there is little information on the effect of Diet-Induced Weight Loss on sperm parameters.…”
Section: Discussionmentioning
confidence: 87%
“…It concluded that it did not affect sperm volume, alertness, total number, morphology, motility or viability [ 29 ]. Another study by Inka et al [ 30 ] showed no effect of bariatric surgery on sperm count or sperm attention at any time during the study period. Likewise, there is little information on the effect of Diet-Induced Weight Loss on sperm parameters.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Moreover, in a Japanese cross-sectional study of 564 newlywed men, subjects with poor semen quality showed higher age, BMI, and higher fasting blood glucose [ 31 ]; erectile function resulted as an independent predictor for poor semen, confirming the association between the two variables in non-diabetic men. Furthermore, in a recent longitudinal study of 12 patients undergoing obesity surgery, sexual function improved after 18 months of follow-up, without effects on semen parameters even after a significant weight loss (from 42.37 ± 4.44 to 29.6 ± 3.77 kg/m 2 ) [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…As of 2023, there are several bariatric surgery procedures commonly performed, including sleeve gastrectomy (SG), one-anastomosis gastric bypass (OAGB), and Roux-en-Y gastric bypass (RYGB). Bariatric surgery was also shown to have a positive effect on sexual satisfaction and erectile function [ 3 , 4 , 5 , 6 ]. This may be related to weight loss [ 7 , 8 ] and overall improved body image [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%